Exploring changes in the lives of BRAC women: a gender perspective - Mahbub, Amina (BRAC Research and Evaluation Division (RED), 2020)
This qualitative study conducted (to explore the changes in ideology, attitudes and aspirations of the rural women involved with BRAC Village Organizations (VO) with "- respect to gender equity.' Being a part of BRAC-ICDDR,B Joint Research Project, the study was conducted in three villages of Matlab Thana. Data collection techniques included life histories for case studies, key informant interview and group discussion. <the study revealed important changes in the thought and ideology of BRAC women compared to the non-BRAC women. BRAC women however, appeared to be in a transition period as indicated by contradictions and confusions between they thought and what they actually practiced. Certain factors had a great influence on BRAC women's thought and ideology which were absent in the lives of non-BRAC women like social and legal awareness training, credit, mobility, work load etc. Pathways through which changes in views on gender equity were explored. The study concludes that development interventions like BRAC's Rural Development Programme (RDP) were contributory in a tangible fashion to the transformation of patriarchal ideology and attitude.